Inkjet printing of dielectric layers with high relative permittivity for digital microfluidics - Schoenfelder, T.; Kemper, F.; Pohle, L.; Reif, M.; Tienken, M.; Beckert, E.; Tuennermann, A. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2021)
Digital microfluidics (DMF) is an emerging technology for liquid-handling of picoliter-to microliter-sized droplets. It enables individual control over droplets by applying electrical fields to an array of electrodes. Standard DMF devices include four key components: substrates, electrodes, a dielectric layer and hydrophobic layers. This work outlines the fabrication of dielectric layers with a high relative permittivity by inkjet printing. The layers consists of OrmoComp, silver nanoparticles and different solvents. OrmoComp has a relative permittivity of about 2.5. By adding 24.2 vol% of silver nanoparticles the relative permittivity rises to 76. Thereby the operating voltage can be reduced drastically.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Dielectric; High-k; Inkjet; Lab-on-a-Chip; Microfluidics; Nanoparticles; Permittivity; Printing